Remarkable increase in Interleukin-5 receptor expression beyond tissue eosinophils in inflammatory bowel disease - Kim, You Ie; Oh, Hyeon Jeong; Yang, Hye Ran (Frontiers in Immunology, 2025)
IntroductionThe role of tissue eosinophils and their relationship with interleukin-5 in gastrointestinal disorders have not been elucidated. This study aimed to analyze tissue eosinophils and interleukin-5 receptor-α subunit (IL-5RA) expression on eosinophils in inflammatory bowel disease (IBD).MethodsBlood and stool test results and radiologic and endoscopic findings in pediatric patients, who were newly diagnosed with IBD, eosinophilic gastrointestinal diseases (EGIDs), or disorders of gut–brain interactions were retrospectively reviewed. Tissue eosinophil counts were analyzed, and immunohistochemistry was performed using an antibody against IL-5RA expressed on eosinophils in the colonic mucosa.ResultsThe tissue eosinophil count and IL-5RA-expressing eosinophil density were significantly different among the three groups (P<0.005). IL-5RA expression was significantly higher in the IBD group than in the EGID group (P<0.001). In IBD, tissue IL-5RA expression was positively correlated with platelet count, erythrocyte sedimentation rate, and highly sensitive C-reactive protein, and negatively correlated with hemoglobin and albumin. In Crohn’s disease (CD), higher IL-5RA expressions were observed with higher pediatric CD activity index (P<0.005). The optimal cut-off value for IL-5RA-expressing eosinophil density was 69.4/high-power field.DiscussionThe expression of IL-5RA in tissue eosinophils is elevated in treatment naïve IBD. IL-5RA expression may reflect disease severity and its extent of involvement in early active CD.